3′-End cDNA Pool Suitable for Differential Display from a Small Number of Cells. (May 1998) - Zhao, S.; Molnar, G.; Zhang, J.; Zheng, L.; Averboukh, L.; Pardee, A.B.
We have generated a 3′ cDNA pool from the RNA of only 1000 or fewer cells by reverse transcription (RT) from an extended oligo(dT) primer with a 3′ degenerate base and a second strand primer with four degenerate 3′bases, followed by PCR. Reproducible differential displays (DD) can be made from this essentially inexhaustible source of DNA. The method produced DD patterns that are comparable but not identical in band number and size distribution with those obtained by the original RT-DD technique. Northern blots performed with the excised bands verified altered gene expressions. The data indicate that this 3′-end cDNA pool can supplement current PCRbased methods of expression genetics. This pool of cDNA sequences also provides a reliable source for primer-specific gene amplifications.